Analisis Tingkat Kecacatan Komponen End Wall Menggunakan Metode QCC dan FMEA di PT INKA (Persero) - Nufaisah, Nurah; Aryanny, Enny (Universitas Nahdlatul Ulama Blitar, 2025)
PT INKA (Persero) is the first integrated train manufacturing company in Southeast Asia. One of the train products currently being worked on is a 612-car passenger train. However, in the production process defects are often found. The end wall component produces the highest defects with a defect percentage of 10.8%. This research uses the Quality Control Circle method and Failure Mode and Effect Analysis at PT INKA (Persero) to determine the level of defects and provide suggestions for improvement. The results of the research show that the percentage level of end wall defects is end wall flatness exceeding tolerance (38%), wavy end walls (33%), and end wall scratches (29%). Recommendations for improvement given are based on the five highest RPN values, namely supervision and pressure of the welder during briefings to regulate and maintain the stability of the amperage and voltmeter according to the WPS used, making a routine schedule to monitor the performance of the welder and the welding process, providing manual procedures or guidelines that are easy to understand. and accessed by the welder, the use of auxiliary tools such as jigs (fasteners) and fixtures (holding devices), and providing sufficient rest time and making the system appreciated or recognized for good performance.